2006
DOI: 10.1007/s10495-006-5115-1
|View full text |Cite
|
Sign up to set email alerts
|

Programmed cell death of stressed keratinocytes and its inhibition by vitamin D: The role of death and survival signaling pathways

Abstract: The epidermis is confronted with multiple environmental and pathophysiological stresses. This study shows that TNFalpha, oxidative stress, hyperosmotic and heat shock induced both caspase-dependent and independent cell death in human HaCaT keratinocytes. The hormonal form of vitamin D, 1,25(OH)2D3, which is an autocrine hormone in the epidermis, protected the cells from all the examined stresses and pathways leading to cell death. We aimed to define the signaling pathways that determine the life-death balance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
35
0
9

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 47 publications
6
35
0
9
Order By: Relevance
“…These studies suggested that 25(OH)D 3 had broad protective effects in many stress model systems. Consistent with our data, the active metabolite of vitamin D 3 , 1,25(OH) 2 D 3 , has been previously reported to protect cells from cell death induction through various pathways including stress [Riachy et al, 2005;Zhang et al, 2005;Diker-Cohen et al, 2006]. In HaCaT keratinocytes, 1,25(OH) 2 D 3 protected the cells from all the examined stress mediated pathways leading to cell death, including TNFa, oxidative stress, hyperosmotic, and heat shock-induced cell death [Diker-Cohen et al, 2006].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These studies suggested that 25(OH)D 3 had broad protective effects in many stress model systems. Consistent with our data, the active metabolite of vitamin D 3 , 1,25(OH) 2 D 3 , has been previously reported to protect cells from cell death induction through various pathways including stress [Riachy et al, 2005;Zhang et al, 2005;Diker-Cohen et al, 2006]. In HaCaT keratinocytes, 1,25(OH) 2 D 3 protected the cells from all the examined stress mediated pathways leading to cell death, including TNFa, oxidative stress, hyperosmotic, and heat shock-induced cell death [Diker-Cohen et al, 2006].…”
Section: Discussionsupporting
confidence: 91%
“…In support of our results, 1,25(OH)2D 3 has been shown to decrease the formation of apoptotic cells in epidermis exposed to UV [Hanada et al, 1995] and to reduce cell death in growing hair follicles following treatment with chemotherapeutic drugs [Schilli et al, 1998]. The hormone also protected keratinocytes in vitro from UVB-and TNFa-induced cell death [Diker-Cohen et al, 2006]. As for the protective effect of 25(OH)D 3 in breast epithelial cells, this is the first report to document its anti-stress action.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…4B), indicating that JNK is essential for MMP-9 induction by the cytokine. In accordance with our previous results (Ravid et al, 2002;Diker-Cohen et al, 2006), we confirm here that calcitriol attenuated the activation of JNK by TNFa under conditions relevant to MMP-9 induction (Fig. 4C).…”
Section: The Involvement Of Jnk and P38 Mapk In The Regulation Of Mmpsupporting
confidence: 93%
“…Some conditions such as the acute or chronic exposition to UV radiation, dehydration, mechanical lesion, changes in the environment temperature or endogenous insults as inflammation and hypoxia can produce oxidative stress in cells 12 . An aggression example that gathers several conditions implicated in oxidative stress is skin burn, and depending on the extension and the proportion of tissue loss, may lead to unacceptable consequences in a hemodynamical and functional context.…”
Section: Discussionmentioning
confidence: 99%